Arabic Loanword In Makassar Language: A Lexicographical Approach Based On Dictionary - Islamiyah Sulaeman; Nur Hasaniyah (Universitas Negeri Makassar, 2023)
Abstrak. Makassar language does not escape the influence of foreign languages in the world. One of the foreign languages that has influenced the Makassar language is Arabic. For this reason, research was carried out to describe Arabic loanword vocabulary in Makassar language through a lexicographical approach to the Makassar-Indonesian dictionary, using a qualitative descriptive research method. Researchers collected data using note-taking techniques and literature techniques, analyzed and made conclusions using the distribution method and the translational equivalent method. Data are grouped based on suitability of pronunciation and meaning. This study found that there were 65 Arabic loanwords in the dictionary, of which 38 loanwords were religious words, while 27 loanwords were general in nature. Some of the Arabic loanword vocabulary in Makassar language has changed letters and consonants which are adapted to the presence of letters and the phonological tendencies of Makassar language speakers. The results of this study contribute to applied linguistics, especially lexicographic studies, which shows the intervention of Arabic in the development of Makassar language structure. Keywords: Loanword, Arabic, Makassar Language